The use of controlling in organizations operating in Poland, Switzerland and the USA – a comparative study - Bieńkowska, Agnieszka; Tworek, Katarzyna (Stosowanie controllingu w organizacjach funkcjonujących w Polsce, Szwajcarii i USA – analiza porównawcza, 2020)
The purpose of the article is to provide knowledge on the similarities and differences in the use of controlling in organizations operating in Poland, Switzerland and the USA along with the main conditions of this use. This comparison in the indicated countries – so far not undertaken in the presented scope in the literature – is justified because controlling has not only a different history there, but also various solutions. The hypotheses formulated for the purpose of achieving the indicated goal were empirically verified on a sample of 2829 organizations: 1683 operating in Poland, 899 in Switzerland and 247 in the USA. Statistical analysis methods were used, including correlation analysis as well as a one-way analysis of variance and t-student analysis and χ2 test analysis. The presented results of the empirical research allow to show similarities and differences in the use of controlling in organizations functioning in the three examined contexts
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 38-48